Knowledge, attitude, and practices regarding periodontal health in patients visiting a dental teaching hospital - Aryal, Deepa; Pandey, Nashib; Neupane, Kamana; Rijal, Arjun Hari; Dhami, Bhageshwar; Bhattarai, Rosina (Journal of Kathmandu Medical College, 2021)
Background: Periodontal diseases, despite being preventable have an increasing prevalence worldwide. Mechanical plaque control methods are most effective to prevent and control these diseases. Objectives: To assess the knowledge, attitude, and practices regarding periodontal health among patients visiting department of Periodontics, Kantipur Dental College and Hospital. Methods: An analytical cross-sectional study was conducted by administrating pretested questionnaire to 384 patients in Kantipur Dental College and Hospital from Sep 2020 to Aug 2021. The study was conducted for one year after taking ethical clearance. All the patients who first visited the department of Periodontics were requested to participate by convenience sampling method. Statistical analysis was done to correlate among knowledge, attitude, and practices. Results: Positive attitude and practices towards dental floss 165 (43%), tongue cleaning 273 (71.1%), replacing tooth brush 268 (69.8%), and regular dental visits 202 (52.6%) was demonstrated. There was lack of knowledge on interdental brushes 79 (20.52%), probiotics 52 (13.5%), gingival massage, and their use to improve periodontal health 17 (4.4%). Conclusion: The majority of the respondents had good oral hygiene practices with favourable knowledge and attitude with respect to periodontal health and its measure to control the disease. Various preventive programs must be conducted regularly to brush up their knowledge. Further improvements should be focused on knowledge and attitude which can increase and improve the practice of oral health.